PENGARUH PENERAPAN MODEL PEMBELAJARAN NUMBERED HEAD TOGEHTER (NHT) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SEKOLAH MENENGAH PERTAMA - Nurashri Partasiwi (Prodi Pendidikan Matematika, STKIP PGRI Bandar Lampung, 2020)
This study aims to know the effect of applying Numbered Head Together learning models to mathematics learning outcomes. The Numbered Head Together learning model is a learning model that assigns numbers to groups or provides opportunities for students to share ideas and consider the most appropriate answers. This research uses the experimental method. The population in this study were all eighth grade students of SMP Negeri 4 Negeri Agung, it has two classes with a total of 66 students. Samples were taken using a total sampling technique, which consisted of 2 classes, namely the VIII1 as an experimental class that learned through the Numbered Head Together learning model and the VIII2 as a control class that using conventional model. Data collection techniques using test, namely in written tests in the form of essays, with a total of 10 items. Data analysis was used using the t-test formula. Based on the results of data analysis that the researchers have done, the results show that t cal = 4.76, and from the distribution table t at a significant level of 5% obtained tf = 2.00. These results remind that t cal > t tab. The results showed that the average score of experimental class was 74.94 while the control class was 62.18. From the results of research and data analysis, it can be concluded that the Numbered Head Together learning model has a positive effect on mathematics learning outcomes for VIII grade students of the even semester of SMP Negeri 4 Negeri Agung in the academic year of 2018/2019.